2016
DOI: 10.1111/ecc.12492
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' experiences of living with cancer: a phenomenological study

Abstract: There is a paucity of knowledge about fathers' experiences of cancer. This study explored the experiences of fathers diagnosed and living with cancer while also having parental responsibility for children. A hermeneutic phenomenological approach guided the study. Data were generated through 22 in-depth interviews with 10 fathers throughout Northern Ireland. The findings evidenced that fathers' identities are challenged and frequently re-shaped by the cancer experience, in many cases leading to an improved life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Future studies should include the viewpoints of patients and their relatives, of their spouses and children, for example through case‐based, serial qualitative interviews and observations across the treatment trajectory of cancer patients. Finally, there is a paucity of knowledge regarding gender aspects influencing communication during parental illness, which future studies might also address, for example what fathers’ experiences and needs are (O'Neill, McCaughan, Semple, and Ryan ().…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include the viewpoints of patients and their relatives, of their spouses and children, for example through case‐based, serial qualitative interviews and observations across the treatment trajectory of cancer patients. Finally, there is a paucity of knowledge regarding gender aspects influencing communication during parental illness, which future studies might also address, for example what fathers’ experiences and needs are (O'Neill, McCaughan, Semple, and Ryan ().…”
Section: Discussionmentioning
confidence: 99%
“…In the case of men presenting with HF their masculinity that is generally defined as the common understanding of the meaning of being a man, in how to behave, how to present oneself, and so forth, is influenced by the sociocultural context that defines masculinity. [8][9][10][11] The manner in which men engaged with heath care systems was shaped by their masculinity and also shaped their decision-making processes relating to the use of health services. [8,9] Other studies revealed that the negative effects of symptoms, depression and anxiety, resulted in low self-worth and feelings of guilt.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been acknowledged that men and woman can have similar cancer experiences, the manner in which men respond may be very different to women (Robertson, 2007). In addition, the changing patterns of family structures and relationships may make open communication more challenging (O'Neill et al, 2016). The findings in this study point to the importance of taking a family centred approach to talking about cancer with the children O'Neill et al, 2016;Turner, Clavarino, Yates, Hargraves, Connors, Hausmann, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…Research has indicated that when a parent is diagnosed with cancer they face additional fears and anxieties as they attempt to simultaneously manage their role as parent, with their illness (Rauch & Moore, 2010;Semple & McCance, 2010a;O'Neill, McCaughan, Semple, Ryan, 2016). Parents have reported difficulties in knowing how to communicate appropriately with their children throughout the illness trajectory (O'Neill et al, 2016;Semple & McCance, 2010a, 2010b and they are primarily focused on protecting or shielding their children from the illness. Understandably parents can become overwhelmed and experience significant parental stress impacting on their psychological wellbeing, in some cases leading to depression (Kirsch, Brandt, Lewis, 2003;O'Neill et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation